Communication Patterns of Narcotics Residivists in Growing a Positive Self-Concept (Case Study of Narcotics Residivists in Detention Cells Directorate of Prisoner Treatment and Evidence - Riadi, Mulia; Pohan, Syafruddin; Zukarnain, Iskandar (PT FORMOSA CENDEKIA GLOBAL, 2024)
This articles aims to analyze how the communication patterns of narcotics recidivists foster a positive self-concept. This research uses qualitative research with a field study approach. The primary data source in this research is the results of interviews and observations with narcotics recidivists and the North Sumatra Regional Police. The data collection techniques used in this thesis are in-depth interviews, observation and documentation. The results of the research show that there are two communication patterns that occur, namely interpersonal communication between recidivists and guards, and intrapersonal communication for emotional management. However, there are obstacles in implementing this positive self-concept. These barriers include two primary factors, namely the interaction of the recidivism environment and economic needs.